ICARU-FB: An IEC 61499 Compliant Multiplatform Software Infrastructure - Rosso R.S.U.* (2016)
© 2016 IEEE.This paper presents the proposal and implementation of I CAN RUn - Function Blocks (ICARU-FB), a multiplatform environment capable of running the function blocks defined in IEC 61499 on architectures with few computational resources. A virtual machine was designed and implemented to perform networks of function blocks on 8-bit platforms with minimal resources. It was also reported to run on a 64-bit computer. Two case studies were performed in order to verify compliance with IEC 61499. Through the case studies, it was verified that it is possible to meet the requirements of the standard, such as configurability, interoperability, and portability. The case studies also demonstrated the ability of the environment to reconfigure the software at runtime.